Project Based Learning in Tourism Subjects to Increase Student’s Academic Motivation and Life Skills - Muh. Anwar; Yusri Yusri; Mantasiah R. (Universitas Negeri Makassar, 2022)
Abstract This study aims to determine the effect of the project-based learning model that is integrated into tourism courses in increasing student academic motivation and life skills. This study used a quasi-experimental approach involving 1 experimental class and 1 control class. The intervention process was carried out for 6 meetings, where the duration of each meeting was 2 hours. The participants in this study were 41 students majoring in German Education which were divided into a control class (20 students) and an experimental class (21 people). Students' academic motivation was measured using a scale developed by Vallerand et al. (1992) consisting of 28 items that had been translated into Indonesian and tested by Natalya & Purwanto (2018). The learning outcome variable was developed by the researcher in the form of a multiple choice test consisting of 25 questions. This learning outcome test has been validated by 2 lecturers who are experts in learning evaluation. The life skill variable was measured using students' perceptions regarding the extent to which the influence of the Project Based learning model could improve their life skills. Data were analyzed using descriptive statistics and inferential statistics. Research findings indicate that the integration of the Project Based learning model in learning tourism courses can increase students' academic motivation. Increased academic motivation directly has an impact on improving student learning outcomes. In addition, the Project Based learning model can have a positive influence on students' life skills.